Exploring EFL university learners’ acquisition of advanced reading skills in the Yemeni context - Ahmed, Waleed Mohammed A. (Universitas Pendidikan Indonesia, 2021)
Reading is an essential language skill for enhancing learners’ performance at various levels of study. However, EFL learners at the tertiary level encounter reading difficulties, particularly in acquiring advanced reading skills, which have affected their reading comprehension and resulted in low academic performance achievement. This is probably attributed to various factors, including learners’ lack of effective reading strategies. A study that exclusively explores reading difficulties encountered by EFL university learners, reasons for the difficulties, and strategies adopted to overcome the difficulties and develop advanced reading skills seem to be scarce in the literature. Therefore, the main purpose of this study was to explore the acquisition process of advanced reading skills in EFL tertiary context at a private university in Yemen from learners’ perspective. The study adopted a qualitative approach to gather data from EFL tertiary learners through a focus group discussion. The data were analyzed manually using the indexing approach. Findings revealed that learners face reading difficulties such as inference making, getting the gist of the text, and managing the reading tasks. These difficulties were attributed to linguistic and non-linguistic reasons, and metacognitive, cognitive, and social-affective strategies were used in reading. The study recommends engaging EFL learners in intensive and extensive reading to help them apply the strategies they learn and develop advanced reading skills and better academic performance. Future research studies may focus on strategies for reading fluency.